“There’s theology and then there’s the people I love. . .”: Authority and Ambivalence in Seminarians’ Attitudes Toward Same-Sex Relationships, Marriage, and Ordination - Johnston, Erin F. ca. 20./21. Jh.; Holleman, Anna; Krull, Laura M. (2024)
Drawing from 102 in-depth interviews conducted with first-year Master of Divinity (M.Div.) students at a Mainline Protestant seminary, this paper examines how students describe and account for their positions on homosexuality, same-sex marriage, and the ordination of gay and lesbian clergy. We found that students on “both sides”—i.e., those who lean affirming and those who lean non-affirming—invoked three primary authorities in their accounts: Biblical authority, Godly authority, and the authority of lived experience, as demonstrated in the lives of gay and lesbian people. We also found that nearly one-third of the students in our sample expressed uncertainty, ambivalence, and/or contradictions in their responses. Through a close analysis of these accounts, we show that ambivalence and uncertainty are rooted in attempts to navigate and “reconcile” the pulls of these different authorities and that attitudinal certainty is often accomplished by privileging one authority over others.